APA CARA-CARA TERBAIK MENCEGAH PERUNDUNGAN DI SEKOLAH - Diana Divecha (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2021)
All 50 states in the United States require schools to have bullying prevention policies in place. But the policy itself is not enough. Despite that obligation, there still appears to be a slight increase in the various forms of bullying over the past three years. Bullying can take the form of an experienced senior basketball player bullying a new player in front of referees, a child who constantly stigmatizes an immigrant classmate because of cultural differences, or a high school student who is suddenly humiliated and ostracized from her peer group. Bullying happens everywhere, even in the best performing schools, and it hurts everyone involved, from the target audience to the observers, and even the bullies themselves. October is national bullying prevention month, so it's a good time to ask ourselves: What is the best course of action to prevent bullying in schools? That's the question I explored with my friend Marc Brackett of the Yale Center for Emotional Intelligence, in a recent paper in which we looked back at dozens of studies of real-world bullying prevention efforts. As we found, not all approaches to bullying prevention are equally effective. Most bullying prevention programs focus on raising awareness of the problem and implementing its consequences. But programs that rely on zero-tolerance punishment have shown ineffectiveness in the United States, and they often disproportionately target students of color. Programs such as peer mediation that give children responsibility for resolving conflicts can increase bullying. (Victims of adult abuse are never asked to resolve it with the perpetrators, and children have additional legal rights to protection because of their developmental status). According to outside observers, even among adults, it only applies to some people—namely, extroverts, who are sympathetic, and those with high social status and strong moral commitments. Many of the approaches adopted by educators have not been evaluated through research, instead educators tend to choose an approach based solely on what their peers have used. We found two research-proven approaches to be the most promising for reducing bullying cases (corresponding to and compatible with other forms of aggression and conflict). The two approaches are a positive school climate and social and emotional learning.